Antischistosomal activity of hederacochiside C against Schistosoma japonicum harbored in experimentally infected animals. Issue 4 (3rd April 2017) - Kang, Nai-Xin; Zhu, Yuan-Jian; Zhao, Jian-Ping; Zhu, Wei-Feng; Liu, Yan-Li; Xu, Qiong-Ming; Zhuge, Hong-Xiang; Khan, Ikhlas A.; Yang, Shi-Lin
Abstract: The present study was undertaken to investigate whether hederacochiside C (HSC) possesses antischistosomal effects and anti-inflammatory response activities in Schistosoma japonicum -infected mice. Different concentrations of HSC were administrated to the mice infected by schistosomula or adult worm by intravenous injection twice a day for five consecutive days. The total worm burden, female worm burden, and the egg burden in liver of mice treated with 400 mg/kg HSC were fewer than those in non-treated ones. Murine immune responses following HSC treatment were investigated using enzyme-linked immunosorbent assays (ELISA). Our results indicated that 200 mg/kg HSC could reduce the expression of IgG, tumor necrosis factor (TNF)-α, interleukin (IL)-4 and IL-17 in comparison to infected group, exhibiting best immunomodulatory effects. In addition, scanning electron microscopical examination revealed that male worms treated with HSC lost their normal surface architecture since its surface showed extensive swelling, erosion, and peeling in tegumental regions. Remarkable amelioration was noticed in histopathological investigations, and 200 mg/kg HSC treatment could reduce the size of granulomatous inflammatory infiltrations in the liver which was reflected in nearly normalization of liver architecture. These results suggested that HSC had potential antischistosomal activity and provided a basis for subsequent experimental.